Pengaruh Penyuluhan Menggunakan E-Booklet tentang Perilaku Seksual Pranikah Terhadap Pengetahuan Siswa - Nafizah, Ainun; Lisnawati, Lisnawati; Nurfatimah, Nurfatimah; Admasari, Yuli; Mangun, Mardiani; Linda, Linda (Bomba: Jurnal Pembangunan Daerah, 2025)
Adolescents are a vulnerable group to premarital sexual behavior due to limited knowledge of reproductive health. At State Senior High School 7 Palu City, education related to premarital sexual behavior remains limited and has not yet utilized systematic digital educational media. This study aimed to examine the effect of health education using an e-booklet on students’ knowledge of premarital sexual behavior at State Senior High School 7 Palu City. This study employed a pre-experimental one-group pre-test–post-test design. The intervention was conducted once by implementing an e-booklet as an educational medium for tenth-grade students. The study was carried out on May 23, 2025, at State Senior High School 7 Palu City. The population consisted of all tenth-grade students (n = 346), with a sample of 78 respondents selected using proportional random sampling. Data were collected using a structured questionnaire and analyzed using univariate and bivariate analyses, with the Wilcoxon test applied for hypothesis testing. The results showed an increase in the proportion of students with good knowledge from 46.2% at pre-test to 100% at post-test. The Wilcoxon test indicated a statistically significant difference between pre-test and post-test scores (p = 0.000; p < 0.05). This study concludes that health education using an e-booklet has a significant effect on improving students’ knowledge of premarital sexual behavior at State Senior High School 7 Palu City. Schools are therefore encouraged to utilize e-booklets as an alternative educational medium to enhance students’ understanding of premarital sexual behavior.